Reframing Immigrant Resistance Alliances, Conflicts, and Racialization in Italy - Cappiali, Teresa (Research in Migration and Ethnic Relations Series, 2022)
This book focuses on the political participation and grassroots mobilization of immigrants and racialized communities in the European context. Based on extensive data collected in Italy, it explores the role that alliances among pro-immigrant groups play in shaping political participation, asking why and how immigrant activists mobilize in hostile environments, why and how they create alliances with some white allies rather than others, and what might explain variations in forms of political participation and grassroots mobilization at the local level. Using social movement, critical race, and post-colonial theories, the author examines the ways in which both institutional and non-institutional actors, including immigrant activists, become involved and compete in the local arena over immigration and integration issues, and assesses the mechanisms by which both conventional and non-conventional forms of participation are made possible, or obstructed. By placing immigrant activists at the center of the analysis, the book offers a valuable and novel insider perspective on political activism and the claims-making of marginalized groups. It also demonstrates how pro-immigrant groups can play a role in racializing immigrant activists. A study of the effects on participation in social mobilization of coalitions, conflicts, and racialization processes among pro-immigrant groups and immigrant activists, this volume will appeal to scholars of sociology, political science, and political sociology with interests in migration, ethnic and racial relations, social movements, and local governance.